Going all the way teenage girls' tales of sex, romance, and pregnancy - Thompson, Sharon (Hill and Wang, 1995)
Her brilliant and moving account of what she heard captures teenage girls' first startled responses to the radically new rules of sex and romance and their efforts to shape new ways of being sexual out of such long-standing adolescent preoccupations as popularity, alienation, and best-friendship